2015
DOI: 10.18551/rjoas.2015-11.01
|View full text |Cite
|
Sign up to set email alerts
|

Benefits From Tree Species’ Diversification in Cocoa Agroforests in the Centre Region of Cameroon

Abstract: This paper analyses the profitability of cocoa farmers in the Centre region of Cameroon who wish to diversify their activity by associating inside their orchards several species of domestic fruit trees. Hence, by using linear programming and financial appraisal tools, eight agroforest systems are compared in order to deduct the most beneficial one. The results show that, priority should be given to the most enriched agroforest (Cocoa+Safout+Mango+Ndjansang) which is the most beneficial/productive one for resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Cocoa agroforestry has successfully been used to restore degraded cocoa landscapes and sustainably stabilise cocoa production in Cameroon [21][22][23] and Costa Rica [24,25] by (i) providing shade to young seedlings to improve their survival rates, and (ii) improving chemical and physical properties of soils, as well as enhancing biodiversity in soils. Past studies have shown that cocoa agroforestry can enhance the efficiency of cocoa farms through pests and diseases reduction [26,27], soil fertility improvement [28,29], and yield and profit increase [30,31]. Moreover, shaded cocoa plays an important role in promoting biodiversity conservation, landscape connectivity, and restoration of abandoned or degraded land [24,32].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa agroforestry has successfully been used to restore degraded cocoa landscapes and sustainably stabilise cocoa production in Cameroon [21][22][23] and Costa Rica [24,25] by (i) providing shade to young seedlings to improve their survival rates, and (ii) improving chemical and physical properties of soils, as well as enhancing biodiversity in soils. Past studies have shown that cocoa agroforestry can enhance the efficiency of cocoa farms through pests and diseases reduction [26,27], soil fertility improvement [28,29], and yield and profit increase [30,31]. Moreover, shaded cocoa plays an important role in promoting biodiversity conservation, landscape connectivity, and restoration of abandoned or degraded land [24,32].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from... to understand and are therefore very much favoured in programme evaluations. CBA, already used in different scientific works (Folefack et al, 2021 ;Folefack et al, 2015 ;Norton, 2013 ;Victor et al, 2010), allows us to analyse the effects of certification on cocoa farmers by measuring their performance against non-certified producers.…”
Section: Methodsmentioning
confidence: 99%
“…Introduced to Cameroon since 1887 by the German colonial administration, cocoa is of considerable economic importance (Ngwang et Meliko, 2021). Indeed, in 2010, cocoa brought in more than 250 billion CFA francs to the state's revenues, or about 3 % of the gross domestic product (Folefack et al, 2015) and provides a living for an average of four hundred and fifty thousand farmers (Lescuyer et al, 2019). There are four major production basins in Cameroon, the South West with 50 % of national production, the Centre (35 %), the South (10 %), and the East (5 %) (Langrand, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although full-sun cocoa is the widespread cocoa farming practice, western and eastern cocoa belts are becoming favorable to the adoption of cocoa agroforestry due to erratic rainfall and the promotion of good agricultural practices (GAP) from extension services. Some farmers are conducting agroforestry-led farming by interplanting trees in cocoa plantations with the bene t of increasing yields (Owusu and Frimpong 2014; Folefack et al 2015), improving soil fertility (Isaac et al 2007), reducing pests and diseases including cocoa swollen shoot virus disease (CSSVD) (Andres et al 2018) and diversifying incomes .…”
Section: Introductionmentioning
confidence: 99%